Epileptogenesis - Herman, Susan T. (Henry Stewart Talks, 2011)
Introduction, Causes of epilepsy, Epileptogenesis, Initial insult / Acute symptomatic seizures, Latent period, Late seizures, Epilepsy, Animal models of epileptogenesis, Risk of epilepsy after brain insults, Clinical trial design, Review of prophylaxis trials, Future directions